Overexpression of Fgf18 in cranial neural crest cells recapitulates Pierre Robin sequence in mice - Lv, Yi; Wang, Qian; Lin, Chensheng; Zheng, Xi; Zhang, Yanding; Hu, Xuefeng (Frontiers in Cell and Developmental Biology, 2024)
The pivotal role of FGF18 in the regulation of craniofacial and skeletal development has been well established. Previous studies have demonstrated that mice with deficiency in Fgf18 exhibit severe craniofacial dysplasia. Recent clinical reports have revealed that the duplication of chromosome 5q32-35.3, which encompasses the Fgf18 gene, can lead to cranial bone dysplasia and congenital craniosynostosis, implicating the consequence of possible overdosed FGF18 signaling. This study aimed to test the effects of augmented FGF18 signaling by specifically overexpressing the Fgf18 gene in cranial neural crest cells using the Wnt1-Cre;pMes-Fgf18 mouse model. The results showed that overexpression of Fgf18 leads to craniofacial abnormalities in mice similar to the Pierre Robin sequence in humans, including abnormal tongue morphology, micrognathia, and cleft palate. Further examination revealed that elevated levels of Fgf18 activated the Akt and Erk signaling pathways, leading to an increase in the proliferation level of tongue tendon cells and alterations in the contraction pattern of the genioglossus muscle. Additionally, we observed that excessive FGF18 signaling contributed to the reduction in the length of Meckel’s cartilage and disrupted the development of condylar cartilage, ultimately resulting in mandibular defects. These anomalies involve changes in several downstream signals, including Runx2, p21, Akt, Erk, p38, Wnt, and Ihh. This study highlights the crucial role of maintaining the balance of endogenous FGF18 signaling for proper craniofacial development and offers insights into potential formation mechanisms of the Pierre Robin sequence.